1989
DOI: 10.1577/1548-8659(1989)118<0195:efitea>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic Fissures in Teleost Eyes and Their Possible Role in Detection of Polarized Light

Abstract: The persistence of the embryonic (optic) fissure into adulthood and development of the falciform process in the eye varied among three fish species: guppy Poecilia reticulata, Mozambique tilapia Tilapia mossambica, and brown trout Sal mo trutta. The falciform process is a ridge of pigmenied and vascular tissue associated with the embryonic fissure in teleosts. In guppies, the embryonic fissure closed during embryonic development, and no falciform process developed. In Mozambique tilapias, the embryonic fissure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
1

Year Published

1993
1993
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 8 publications
0
15
1
Order By: Relevance
“…Figs, la and lc), and never parallel to it, as would be expected if new retina had been added along this contour. In contrast, Ahlbert (1976) and Kunz and Callaghan (1989) have claimed that the edge of the fissure is a proliferative zone, but their evidence (a band of differentiating cells restricted to the temporal side of the fissure) implies an asymmetry opposite to what we have shown. It seems likely that they have described the "dorsal hook" region ( Fig.…”
Section: Cone-photoreceptor Mosaic-implications For Retinal Growthcontrasting
confidence: 99%
“…Figs, la and lc), and never parallel to it, as would be expected if new retina had been added along this contour. In contrast, Ahlbert (1976) and Kunz and Callaghan (1989) have claimed that the edge of the fissure is a proliferative zone, but their evidence (a band of differentiating cells restricted to the temporal side of the fissure) implies an asymmetry opposite to what we have shown. It seems likely that they have described the "dorsal hook" region ( Fig.…”
Section: Cone-photoreceptor Mosaic-implications For Retinal Growthcontrasting
confidence: 99%
“…At all stages, the peripheral regions of the retina were prominent and well developed, but, as revealed by serial sectioning, also contained some novel structures which, to our knowledge, were not previously described. Firstly, a very prominent rete mirabile consisting of tightly packed vascular tissue extended from the posterior portion of the globe, where it is expected for teleosts, to project from a region adjacent to what we interpret as a peripheral embryonic fissure (Kunz & Callaghan, ) and what appeared to be a separate retinal lobe. This peripherally located, pigment epithelium circumscribed portion of retina that was physically separated from the main retina, might represents a C. lumpus version of an accessory retina, reminiscent of that described previously in deep sea fish (Partridge et al ., ; Wagner et al ., , ).…”
Section: Discussionmentioning
confidence: 99%
“…In teleostean eyes, there are reports of a total closure of the embryonic fissure in some species and the partial closure of it in others (Hanyu 1959, Kunz & Callaghan 1989. In N. rupicola, there appears to be no trace of a fissure in adult eyes and it might be that the hyaloid artery entered the vitreous cavity before the total obliteration of the fissure during embryonic development.…”
Section: Discussionmentioning
confidence: 99%
“…hyaloid artery), Walls (1942) suggested that they are mutually exclusive for a given teleostean retina. This has been substantiated in several species (see e.g., Hanyu 1959, 1962, O'Connell 1963, Ali et al 1968, Sivak & Roth 1978, Munk 1984, Kunz et al 1985, Kunz & Callaghan 1989. Franz (1934) andlater Walls (1942) suggested that vitreal vessels may nevertheless occur in association with a falciform process which is restricted to the distal end (close to ora terminalis) of the retina, projecting rather less conspicuously into the vitreous cavity (the so-called low falciform process after Hanyu's classification, see Hanyu 1962).…”
Section: Introductionmentioning
confidence: 93%